Familial DHCR7 genotype presenting as a very mild form of Smith‐Lemli‐Opitz syndrome and lethal holoprosencephaly. Issue 1 (9th August 2020) - Temple, Suzanna E. L.; Sachdev, Rani; Ellaway, Carolyn
Abstract: Smith‐Lemli‐Opitz syndrome (SLOS) is an autosomal recessive metabolic disorder caused by variants in the DHCR7 gene. In cholesterol biosynthesis, 7‐dehydrocholesterol (7‐DHC) is converted to cholesterol by the enzyme 7‐DHC reductase, which is encoded by the gene DHCR7 . Thus, an elevated 7‐DHC is indicative of SLOS. Characteristically SLOS is usually associated with congenital anomalies, dysmorphisms, and moderate to severe neurodevelopmental delay. However, there are rare descriptions of individuals with milder phenotypes. We report a mild case of SLOS presenting with short stature, cleft palate, imperforate anus, and mild language delay with subtle dysmorphic features. 7‐DHC was not elevated at 1 year of age and SLOS considered excluded at this time. The parents had two pregnancies with holoprosencephaly. Whole exome sequencing of one of the fetuses identified compound heterozygous pathogenic variants in the DHCR7 gene (c.964‐1G>C (p.?) and c.1039G>A (p.Gly347Ser) causative of SLOS. The proband with a mild form of SLOS was also found to have the same DHCR7 variants as the fetus and repeat testing of 7‐DHC at 4 years of age was elevated, in keeping with SLOS. This case is the first to describe a wide intrafamilial phenotypic spectrum of SLOS as a result of the same DHCR7 genotype. This case also supports the findings of others that a normal or near normal development should not exclude SLOS. As demonstrated in this case exclusion of a metabolic diagnosis because of a negative biochemical marker such as 7‐DHC is not absolute and if clinical suspicion remains genomic sequencing is warranted.